Yield and performance analysis of the first grid-connected solar farm at Moshoeshoe I International Airport, Lesotho. (September 2015) - Mpholo, Moeketsi; Nchaba, Teboho; Monese, Molebatsi
Abstract: The performance of a newly installed 281 kWp first grid-connected photovoltaic solar farm in Lesotho is evaluated against the basic parameters stated in the International Electro-Technical Commission (IEC) Standard 61724 and a number of other studies. The performance parameters selected are those that mainly indicate the suitability of a site for solar power development. Using normalised values, a brief comparison with other farms across the globe is made to assess the relative performance of the farm. The results show that its performance is satisfactory, with a weighted performance ratio of 0.70 compared to the global average of 0.70–0.80 for sufficiently well performing farms. However, the performance could be improved with improved operational monitoring of the farm. Additional performance parameters are assessed relative to the standard and the farms in other countries, such as capture and system losses, system efficiencies, and capacity factors, are above the thresholds for satisfactory performance. Measurements at the site show a high solar energy resource in the range of 4.0–7.2 kWh/m 2 /day. The results show that the area is suitable for grid connected photovoltaic systems. Highlights: Weighted performance ratio of the farm is 0.70 which is at the bottom of the global average range of 0.70–0.80 for sufficiently well performing farms. This is due to lack of remote monitoring. High solar energy resource in the range of 4.0–7.2 kWh/m 2 /day at the site. The monthly average array ( η A ), inverter ( η INV ) and system ( η SYS ) efficiencies vary from 5.6% to 12.5%, 84.3%–90.6%, and 5.05%–11.3%, respectively. The average monthly capacity factor is given by 17.20%, it ranges from 8.7% to 21%.